HUBUNGAN DUKUNGAN TEMAN SEBAYA DENGAN RESILIENSI AKADEMIK MAHASISWA YANG SEDANG MENYUSUN SKRIPSI - Rizki Oktafia, Hanifa; Fitriana, Siti; Yulianti, Padmi Dhyah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
Research on the relationship between peer social support and academic resilience in students who are compiling a thesis in the Guidance and Counseling Study Program, Faculty of Education, PGRI Semarang University is motivated by the number of individuals who experience problems with the process of working on a thesis caused by various things.The purpose of this study was to determine the relationship between peer social support and academic resilience. In this study, the method used was quantitative with the type of correlation research. The sample of this study amounted to 58 students who were working on a thesis in the Guidance and Counseling Study Program, Faculty of Education, PGRI Semarang University, which was taken using the Proportionate Stratified Random Sampling technique. The data collection technique used is a questionnaire scale of self-confidence and emotional intelligence. The results of the Pearson Product Moment test found the sig value. (2-tailed) obtained 0.000<0.05, it can be concluded that there is a significant relationship between peer social support and academic resilience. It is known that the correlation coefficient value r calculated 0.936 with a positive level. This shows that Ha “is accepted and Ho ‘is rejected’. Thus the researcher's hypothesis which states “there is a relationship between peer social support” can be accepted empirically. This means that the higher the peer social support an individual has, the higher the academic resilience will be.